In old Paris : an anthology of source descriptions, 1323-1790 - Berger, Robert W. (Italica Press, 2002)
"In Old Paris is a useful teaching volume, with modest aims which are accomplished tidily. It provides a selection of five descriptions of the city between the fourteenth and eighteenth centuries. There are passages from Jean de Jandun's A Treatise on the Praises of Paris (1323); from Guillebert de Mets's The Description of the City of Paris (early fifteenth century); from A Description of Paris written in the late sixteenth century by the Secretary to the Venetian ambassador in Paris; from Marana's A Pleasant Critique of Paris (1692); and Karamzin's Letters from Paris (1790). The editor tells us that these particular texts have been chosen because "they are the most interesting and vivid descriptions of the city from each of those centuries that are suitable for an anthology." The introductions to each text bring out the vividness of the detail well and also comment on the very different genres to which each text belongs. With the exception of Karamzin, all are made available in English for the first time. The translations look crisp, and the scholarly apparatus comprises a brief appendix on the size and population of Paris, some useful maps, and a fairly lengthy "architectural gazetteer." The latter is a little luxuriant, in a volume less than half of which is primary text, and I would have preferred footnotes to the architectural gazetteer. But these are niggles. All in all, this is a job done well: let us hope that Professor Berger finds an audience." http://www.h-france.net/vol3reviews/vol3no83jones.pdf